Nurses' compliance to patient and environmental safety guidelines in critical care units - Aly Abd Elhamid, Eman; Ezz Eldin Abdallah, Nehad; Mohamed Abd Elrahman, Safaa (International Journal of Advanced Nursing Studies, 2020)
The ability to provide safe and high-quality care to patients is the primary goal and the focus for many health care providers. Guidelines can be used to reduce adverse event in practice and to promote the delivery of high quality and evidence-based health care. The aim of the study to investigate nurses' compliance to patient and environmental safety guidelines in critical care units. Descriptive research design was utilized to achieve the aim of this study. The study was carried out at three of Minia University Hospitals in Minia city. All available nurses (n= 88) who were working in critical care units at time of data collection in the selected hospitals. An environmental and patient safety guidelines questionnaire was used to achieve the aim of this study. Results: less than two third of studied subject were not compliance to patient safety nurses', while nurses complied to environmental safety with 62.5% in critical care units; also, there is highly statistical significance between departments and nurses' compliance to patient safety. Thus, it was concluded that less than two third of studied subject were not compliance to patient safety. As well as environmental safety in critical care units was appropriate with 62.5% in critical care units. Recommendations: Staff development programs for nurses working in critical care units related to patient and environmental safety as well as ensuring that the organizationâ€™s annual budget includes adequate resources to implement and evaluate health and safety activities.Â Â